Nano-niosomes in drug, vaccine and gene delivery: a rapid overview - Abbas Pardakhty; Esmaeil Moazeni (Nanomedicine Journal, 2013)
Abstract Niosomes, non-ionic surfactant vesicles (NSVs), are the hydrated lipids composed mainly of different classes of non-ionic surfactants, introduced in the seventies as a cosmetic vehicle. Nowadays, niosomes are used as important new drug delivery systems by many research groups and also they are effective immunoadjuvants which some commercial forms are available in the market. These vesicles recently used as gene transfer vectors as well. This review article presents a brief report about the achievements in the field of nanoscience related to NSVs. Different polar head groups from a vast list of various surfactants with one, two or three lipophilic alkyl, perfluoroalkyl and steroidal moieties may be utilized to form the proper vesicular structures for encapsulating both hydrophilic and hydrophobic compounds. The methods of niosome preparation, the vesicle stability related aspects and many examples of pharmaceutical applications of NSVs will be presented. The routes of administration of these amphiphilic assemblies are also discussed.